If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y = 6x(x + -1) Reorder the terms: y = 6x(-1 + x) y = (-1 * 6x + x * 6x) y = (-6x + 6x2) Solving y = -6x + 6x2 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Simplifying y = -6x + 6x2
| -430+.35x=.05x-280 | | 10a-5c+12a-8c= | | 5x-2=-1+4x | | 18d+r=100 | | 3y-7=y+1 | | .15y+.08(y+9000)=2100 | | 3n-1=-1-4n | | 1.29x=21+0.99 | | 80.115= | | 4a-3a=19 | | -10+5k=1k-6+2k | | 8x+1=x | | 2x-7=2x-9 | | 3-1r=-7-6r | | 3-6r=-7+4r | | 5n-2=3+6n | | 8x+3=11x-15 | | 5+2p=3+4p-1p | | 3n*7=-36 | | 1x-6=-3x+6 | | 4x-8=4+8 | | 39-3x=9-9x | | 3n+7=-36 | | -2+2a=-5+3a | | 4x+40=11 | | 3v-3+5v=4v+9 | | 1v-6=6+1v-6v | | 1=5/9(f-32) | | 6p-q^2= | | 1=5/9(f-3) | | 2x-y=65 | | 7x-3=3x+10 |